If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + 48 = 0 Reorder the terms: 48 + -12x = 0 Solving 48 + -12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + -12x = 0 + -48 Combine like terms: 48 + -48 = 0 0 + -12x = 0 + -48 -12x = 0 + -48 Combine like terms: 0 + -48 = -48 -12x = -48 Divide each side by '-12'. x = 4 Simplifying x = 4
| 12+0.5+1x=16.75 | | 4t(13t+9)=0 | | -(7y+.6)=3.6-y | | 46=78+16n | | 8(x-3)+7=y | | 2(9c+2)= | | 8(x-3)=y | | 8x-3=y | | 2(b-8)= | | ln(1-x)+ln(4-x)=ln(10) | | 3x+46-x=58 | | 3(a+9)= | | 12+0.5+1x=18.1 | | 18=-4(3x+2)+13x | | 324=8x | | 6(x+7)=6x+7 | | ln(x^2+2x)=lnx | | 12+50+1x=18.1 | | 3.50x=5.50x | | 3.50x=5.50 | | 2-(3x+1)=5x-9 | | x+7-(6-x)=10 | | -2m+8m+1=0 | | 3X^2-12X-135=0 | | -(7y+3)-(-6y-7)=-4 | | 1221=16T^2 | | 4t(13t+9)= | | (x-a)m=y | | 3(x+1)=2x-3 | | v^2-44=-8 | | 24=18-16-14 | | .5(4-2a)=a-1.8 |